Pengaruh Motivasi dan Iklim Psikologi Terhadap Kinerja Pegawai Sekretariat Komisi Pemilihan Umum Kabupaten Majene - Azima, Fauzan; Magfirah, Magfirah; Hafid, Haeruddin; Supu, Ramli; Karim, Ahmad; Ikram, A. Aiyul (Universitas Sulawesi Barat, 2023)
Psychological climate describes the climate that exists in an institution that can cause employee members to like their work wholeheartedly or can actually cause psychological barriers to their work. Each agency, such as the General Elections Commission (KPU) has a goal to achieve as much as possible. To achieve maximum goals, good performance is needed from KPU employees. To get good performance from employees, structured and effective direction must be sought. An agency, in an effort to move members to want to work more productively in accordance with predetermined goals, requires motivation which can be seen as a basic drive that moves a person or a desire to devote all energy because of a goal. From this background, in this study there are three problem formulations, namely 1. Does motivation affect the performance of Majene Regency 3 does motivation and psychological climate affect the performance of KPU Majene Regency employees. In this study, researchers used quantitative methods, the specifications were systematic, planned and clearly structured from the start to the creation of the research design. The data used in this study used a survey method by conducting security and the activities and activities of KPU Majene Regency employees. From the results of this study it was concluded that motivation and psychological climate had an effect on the performance of the KPU secretariat staff in Majene Regency. With work motivation and psychological climate, it can be seen that good performance can be achieved more easily.